Air pollution and mortality benefits of the London Congestion Charge: spatial and socioeconomic inequalities. Issue 9 (28th February 2008) - Tonne, C; Beevers, S; Armstrong, B; Kelly, F; Wilkinson, P
Abstract : Objectives: To alleviate traffic congestion in Central London, the Mayor introduced the Congestion Charging Scheme (CCS) in February 2003. We modelled the impact of the CCS on levels of traffic pollutants, life expectancy and socioeconomic inequalities. Methods: Annual average NO2 and PM10 were modelled using an emission-dispersion model. We assumed the meteorology and vehicle fleet remained constant during the pre- and post-CCS periods to isolate changes due to traffic flow. Air pollution concentrations were linked to small area socioeconomic, population and mortality data. Associated changes in life expectancy were predicted using life table analysis and exposure-response coefficients from the literature. Results: Before the introduction of the CCS, annual average NO2 was 39.9 μg/m 3 and PM10 was 26.2 μg/m 3 across Greater London. Concentrations were 54.7 μg/m 3 for NO2 and 30.3 μg/m 3 for PM10 among census wards within or adjacent to the charging zone. Absolute and relative reductions in concentrations following the introduction of the CCS were greater among charging zone wards compared to remaining wards. Predicted benefits in the charging zone wards were 183 years of life per 100 000 population compared to 18 years among the remaining wards. In London overall, 1888 years of life were gained. More deprived areas had higher air pollution concentrations; these areas also experienced greater air pollution reductions and mortality benefits compared to the least deprived areas. Conclusions: The CCS, a localised scheme targeting traffic congestion, appears to have modest benefit on air pollution levels and associated life expectancy. Greater reductions in air pollution in more deprived areas are likely to make a small contribution to reducing socioeconomic inequalities in air pollution impacts.